PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2015) - Robby Heryanto; Agung Juliarto (Diponegoro Journal of Accounting, 2017)
The aims of this research are to analyze (1) the impact of corporate social responsibility disclosure (CSR) on return on assets (ROA), (2) the influence of corporate social responsibility disclosure (CSR) on return on equity (ROE), (3) influence of corporate social disclosure (CSR) on earning per share (EPS) and (4) the impact of corporate social responsibility (CSR) disclosure on net profit margin (NPM) on manufacturing companies listed on the BEI period 2014-2015. CSR disclosure is measured by CSR Indexes based on the 4th generation Global Reporting Initiave (GRI) Index (G4). Profitability is measured by return on equity (ROA), return on equity (ROE), earnings per share (EPS), and net profit margin (NPM).The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2015. The research sample used is manufacturing companies that disclose social responsibility in 2014 and 2015 by using purposive sampling method. There are 68 companies in 2014 and 71 companies in 2015 that meet the criteria as the research sample. The analytical tool used to test the hypothesis is Partial Least Square (PLS)The results show that corporate social responsibility (CSR) has a positive and significant effect on profitability by using net profit margin proxy (NPM), while using return on asset (ROA), return on equity (ROE), earnings per share (EPS) Has no significant effect.